The Relationship Of Production Geology To Exploration (7cfc64bf-da44-4b7c-b26a-5e8458292263) - J. E. Worthington; S. P. Brown (Society for Mining, Metallurgy & Exploration, 1992)
Increasingly, exploration geology seems to be growing into a practice overly separated from production geology, yet the eventual purpose of exploration is a producing mine. To help in the search for new deposits, exploration "lessons" will be drawn from the papers given at the Fall AIME Applied Geology Symposium. In addition, examples will be re-emphasized to show how early observation of matters now routine to mine work (for example, hydrology, rock mechanics, oxidation state) can help increase the effectiveness of exploration.